Prevalence of tooth decay in deciduous and permanent teeth in a schoolchildren population: an epidemiological investigation - Silvia Fanelli; Letizia Lugli; Francesca Chiara De Razza; Francesca Gazzani; Saveria Loberto; Elisabetta Cretella Lombardo; Francesco Fabi; Arianna Malara (Annali di Stomatologia)
Aim: the aim of the present study was to assess the prevalence of dental caries in a population of schoolchildren in Rome (Italy) with different age ranges. Materials and Method: the study involved n.1033 subjects, between 6 and 14 years of age, attending public schools in Rome (Italy). All the subjects included in the study were divided into three different age groups: 6 to 8 years (Group A), 9 to 11 years (Group B) and 12 to 14 years (Group C), respectively. The Group A consisted of n. 385 patients (197 M, 188 F) with a mean age of 6.9±0.8 years; the Group B consisted of n. 355 patients (188 M; 167 F) with a mean age of 10.5±1.2 years; the Group C consisted of n. 293 patients (157 M; 136 F) with a mean age of 12.6±0.9 years. The subjects selected for the study were analyzed about the oral conditions by six expert examiners and the prevalence of dental caries on deciduous or permanent were calculated in each group. The Pearson Chi test was used to perform the statistical analysis. The level of significance was set at P < 0.05. Results: in Group A, most participants were caries free (255 subjects). In children with caries (160 subjects), 126 presented caries on deciduous teeth and 34 on permanent teeth. Similarly, more than half of the students of Group B were caries free (226 patients) and 129 students showed caries on primary (82 patients) and permanent teeth (47 patients). Dental caries on permanent teeth was present in most of the subjects of Group C (35 subjects) and only 10 participants showed caries on primary teeth. In the same group, a good number of participants (248 subjects) were caries free. Conclusions: dental caries is still a major public health concern in the schoolchildren population in Rome. The Results of the current study highlighted that dental screening plays an important role to improve public oral health conditions and involving the school structure means motivating teachers and parents for a good oral hygiene habit. A proper oral hygiene, especially if established at an early age, can translate into benefits in the permanent teeth that can last a lifetime if cared for properly. This underlines the importance of communication with families, which is also one of the main goals of this work.